Annotated list of Tardigrada records from Ukraine with the description of three new species - Pilato, Giovanni; Kiosya, Yevgen; Lisi, Oscar; Inshina, Valentina; Biserov, Vladimir (Zootaxa, 2011)
A list of tardigrade species recorded from the Ukraine is provided; 18 are new records for this geographic area and three, Tenuibiotus bozhkae sp. nov., Xerobiotus euxinus sp. nov. and Hypsibius pallidoides sp. nov. are new to science. Characters for Tenuibiotus bozhkae sp. nov. include two small gibbosities on each hind leg; pharyngeal bulb with three macroplacoids and microplacoid; eggs with long conical processes. For Xerobiotus euxinus sp. nov. there is a narrow buccal tube, dorsal transverse ridges of the buccal armature appear joined together forming a continuous arc; pharyngeal bulb with two macroplacoids and microplacoid, lunules absent on the first three pairs of legs but present on the hind legs; no cuticular bar on the legs. Hypsibius pallidoides sp. nov. has a very narrow buccal tube; pharyngeal bulb with two macroplacoids and a very small, dot-shaped, septulum; claws similar to those of Hypsibius pallidus (i.e. the main branches of the external claws are inserted onto the secondary branch at a distance from the base); lunules and cuticular bar absent from the legs.